2021
DOI: 10.3354/meps13812
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal patterns of carrion biomass of marine tetrapods at the ocean-land interface on the southern Brazilian coastline

Abstract: Quantifying how much carrion is produced temporally and spatially in ecosystems is considered one of the most important aspects of carrion ecology. Marine-derived inputs transferred from the ocean to terrestrial ecosystems are the principal source of energy and biomass for many coastal ecosystems. Here, we provide a comprehensive quantification of the carrion biomass of marine tetrapods across space and time at the ocean-land interface on the Brazilian coastline. Based on 3 large datasets, we estimated carrion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The recovery rates of carcasses during systematic beach surveys also could be influenced by various factors, including carcass decomposition, scavenger activity and removal by locals (Peltier et al, 2012; Tavares et al, 2021). For example, adult cetacean carcasses decompose rapidly in warmer conditions than in cold conditions, and the rate of decomposition is also influenced by body size (Gol'din et al, 2013; Moore et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recovery rates of carcasses during systematic beach surveys also could be influenced by various factors, including carcass decomposition, scavenger activity and removal by locals (Peltier et al, 2012; Tavares et al, 2021). For example, adult cetacean carcasses decompose rapidly in warmer conditions than in cold conditions, and the rate of decomposition is also influenced by body size (Gol'din et al, 2013; Moore et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Strandings rates reflected the seasonality characteristic of the Amazon Estuary and suggested a temporal effect and a human impact in this region. Tavares et al (2021) suggested that strandings of resident marine species such as Guiana dolphins and Franciscana dolphins ( Pontoporia blainvillei ) could be classified as predictable resources in the South and South‐Eastern coasts of Brazil due to their predominance and the constant interaction of these species with fisheries. This predictability could be also assumed for the Northern Brazilian coast, based on the detected temporal variations.…”
Section: Discussionmentioning
confidence: 99%
“…We used fresh carcasses of marine tetrapods (seabirds, sea turtles and cetaceans; Table S1) as biological drifters to simulate their natural trajectories after death at sea. Carcasses were obtained from two sources: (a) beached carcasses (decomposition codes 2 or 3, according to Tavares et al, 2021) found during systematic beach surveys in southern Brazil between 2017 and 2019, or (b) carcasses (decomposition code 2) from a wildlife rehabilitation center. The carcasses were stored frozen at −20°C until the drift experiment and thawed at room temperature for up to 24 h before release.…”
Section: Biological and Nonbiological Driftersmentioning
confidence: 99%
“…In the South Brazil Shelf (SBS) Large Marine Ecosystem (23-34°S), over 55,000 marine tetrapods stranded between 2016 and 2019, many of them coming from bycatch, including threatened species (Tavares et al, 2021). Despite the importance of understanding global patterns of megafauna bycatch for conservation and management efforts, there are still gaps in knowledge that persist (Lewison et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation